Supply chain risks: an automotive case study - Shahbazi, Sasha; Delkhosh, Ali; Ghassemi, Poorya; Wiktorsson, Magnus (Cranfield University Press, 2013)
The supply chain is a complex system exchanging information, goods, material and money within enterprises, as well as between enterprises within the value chain. An effective supply chain management contributes to large corporate profits and it is therefore a valid path to reinforce the enterprises' competitiveness. However, supply chain is exposed to influences from undesirable factors both from the outside environment and the entities in the chain. Moreover, industrial trends towards lean production, increasing outsourcing, globalisation and reliance on supply networks capabilities and innovations, increase the complexity of the supply chain . Therefore, managers need to identify, and manage risks, as well as opportunities, from a more diverse range of sources and contexts. This paper contributes to identify and categorise supply chain risks based on a literature study and an automotive manufacturer’s viewpoint. The empirical results indicate suppliers and raw material prices as the major internal and external potential risks.
Keywords: supply chain management; risk assessment; automotive industry